Intertextuality of Hadith Regarding the Prohibition of Seeking Position - Ansori, Ibnu Hajar; Fiddaroyni, Fatia Salma (Pascasarjana, Universitas Islam Negeri Alauddin Makassar, 2023)
As the development of era, experts in hadith offer various interpretation techniques, for example intertextual techniques, that is studying the meaning of the editorial aspect of hadith by looking at munāsabah with the text of Qur’an and other meaningful hadiths. In this article, this technique was applied to the hadith regarding the prohibition of asking for a position, starting with searching and discussion about authenticity followed by studying the intertextuality of its meaning. The method used is qualitative with the type of literature study presented in an analytical descriptive method. The results of this study lead to the conclusion that the hadith regarding the prohibition of asking for this position is accepted as blasphemy. The study of the intertextuality of the hadith shows that in Islam, it is forbidden to have ambitions to get a position if it is not supported by force. The strong meaning does not only mean physically but also leadership skills, firmness, fairness and wisdom. The importance of strength in carrying out this task or mandate, is also implied in QS. Al-Qaṣaṣ verse 26. In this verse, it is told that the two daughters of Prophet Shu'aib as. asked their father to give certain tasks to the Prophet Mūsā as., because he was a young man who was